Proceedings of the 2006 International Conference on Wireless Communications and Mobile Computing 2006
DOI: 10.1145/1143549.1143705
|View full text |Cite
|
Sign up to set email alerts
|

Exploring power saving in 802.11 VoIP wireless links*

Abstract: Batteries are a primary resource in wireless networks for many mobile devices. Minimizing energy consumption without affecting communication activities is crucial to prolong the lifetime and improve the robustness of the wireless connection. One effective way to reduce energy consumption is to set the entire, or part of the system in a low power mode whenever possible. This paper explores a power saving approach for VoIP and presents a new power saving scheme that does not require extra protocol overhead or mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In fact, users QoE is highly degraded when the packet delays are very high, as the number of late packet loss increase. In [10], the authors tried to compute the sleep period for VoWLAN. The authors considered the VoIP packet inter-arrival and the MAC layer delay variation to deduce the duration of the sleep period.…”
Section: Related Work On Energy Conservation In Wlansmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, users QoE is highly degraded when the packet delays are very high, as the number of late packet loss increase. In [10], the authors tried to compute the sleep period for VoWLAN. The authors considered the VoIP packet inter-arrival and the MAC layer delay variation to deduce the duration of the sleep period.…”
Section: Related Work On Energy Conservation In Wlansmentioning
confidence: 99%
“…By considering a simple 802.11 analytical model as well as a VoIP call using 64kbps (typical bit-rate for G.711 calls), they found that the optimal value of the sleep period is equal to 20ms. In [10] and [11], the authors proposed to derive a dynamic sleep strategy to tune the sleep and the packetization intervals dynamically according to the collision probability of the WLAN. By using the collision probability, the author tried to found out a trade-off between maximizing network capacity and energy conservation.…”
Section: Related Work On Energy Conservation In Wlansmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors measure power consumption incurred for tasks like scanning, roaming, receiving beacons and draw inferences for VoIP applications. This work looks at energy from a micro-level perspective focusing only on the one hop network with the AP; similar micro-level work on the topic has been done by the authors of [12,28]. Our work on the other hand looks at energy from a macro-level perspective focusing on end-to-end (multiple hops over the Internet) characteristics of a VoIP session.…”
Section: Related Workmentioning
confidence: 92%
“…The proliferation of Wi-Fi equipped smart phones promotes the researches that target improving the power saving efficiency of an 802.11 PSM station when it is actively serving Voice over IP (VoIP) sessions [54][55][56][57][58]. In [59][60][61], the authors proposed to utilize proxies to aggregate traffic, thus reducing transmission overhead and energy consumption.…”
Section: Related Work On Psmmentioning
confidence: 99%